A Highly Abundant Lectin Protein in Arabidopsis thaliana Confers Resistance Against Pathogens - Omega, Maria prihtamala; Hall, Skye Thomas; Schenk, Peer; Kobe, Bostjan (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2008)
Lectins are glycoproteins that recognize and bindÂ to specific carbohydrates. they areÂ involvedÂ in a range of biologicalÂ functions,Â suchÂ asÂ plant defence,Â storageÂ proteinsÂ seedÂ germinationÂ andÂ plantÂ microbeÂ interactions. Lectin 3.1Â (At3g 15356) is a protein in plant model , Arabidopsis thaliana, that has been shownÂ to be up-regulated inÂ allÂ defenceÂ pathways, especiallyÂ inÂ responceÂ to methylÂ ester jasmonateÂ (MJ) . AllÂ thal wasÂ knownÂ aboutÂ the geneÂ wasÂ thatÂ itÂ hadÂ goodÂ homologyÂ toÂ theÂ beta domainÂ of legumeÂ lectins. That aim ofÂ thisÂ project wasÂ to characterizeÂ theÂ structureÂ andÂ functionÂ ofÂ theÂ IectinÂ proteinÂ usingÂ CD spectra andÂ X-rayÂ crystallography. AÂ TÂDNAÂ insertionÂ lineÂ for theÂ lectinÂ geneÂ andÂ a number Â of 35SÂ over-expressionÂ linesÂ thatÂ hadÂ varyingÂ levelsÂ of expression had been generated, but none of these showed any obviousÂ phenotype. Two protein bands were observed onÂ Comassie stained SDS-PAGE gelsÂ inÂ the over-expressionÂ lines andÂ in MJÂ induced wild-typeÂ (WT) . TheÂ two protein bands representedÂ twoÂ isoforms ofÂ theÂ lectin 3.1Â protein ; inÂ a glycsylation assay theÂ larger proteinÂ band was shownÂ to be heavily glycosylated . A nematode (M. incognita) disease assay djscoveredÂ that theÂ lectin over-expression linesÂ hadÂ lessÂ nematodeÂ eggsÂ comparedÂ toÂ thatÂ of the WT andÂ thatÂ theÂ insertionÂ lineÂ hadÂ more nematodeÂ eggs Â thanÂ the WT. ThisÂ dataÂ providesÂ evidenceÂ that Â Â lectinÂ 3. 1Â improves. plantÂ resistanceÂ against M. incognita infection.Â interestingly,Â the nematode gutÂ liningÂ containsÂ fucose withÂ whichÂ IectinÂ 3.1 bindsÂ to.Â Keywords: ArabidopsisÂ thaliana,Â lectinâs structure andÂ function, Â pathogen resistance